A IGREJA MESSIÂNICA NA PERIFERIA URBANA DE GUARULHOS, SP: um estudo sobre as práticas, identidade religiosa, marginalidade e corte em uma Nova Religião Japonesa. - ROMÃO, RENAN LESCANO (2018)
The study of religions in the context of urban periphery has grown both in the field of sociology and in the sciences of religion thanks to the perception that it constitutes a privileged space for the analysis of social dynamics. There are, however, few inroads that deal properly with minority, ethnic and transnational religions in the periphery, focusing more on the growth theme of evangelicals and those without religion in these populations. The present work proposes an analysis of practices, identity, marginality and cut principle in two religious’ communities of the World Messianic Church of Brazil, installed in the urban periphery of the city of Guarulhos, SP. The Messianic Church, one of the most popular New Japanese Religions in Brazil, has gained its own Brazilian identity and the study of this in the periphery reveals a series of innovative functions that religion starts to play within this construction. Religious transit, the origin of most of its members, reveals which resources have became important in the transition from an earlier religious identity to "messianic" identity. The incidence of the process of identity marginality, but not necessarily, of the use of "cut" or "split" as a solution to a perceived hybridity among the participants was noted.